2010
DOI: 10.1159/000282114
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of the Adipokine Chemerin in Gestational Diabetes Mellitus

Abstract: Background: Chemerin was recently introduced as a novel adipokine playing a crucial role in adipocyte differentiation and insulin signaling. In the current study, we investigated circulating chemerin levels in patients with gestational diabetes mellitus (GDM) as compared to healthy pregnant controls matched for gestational age and fasting insulin. Methods: Chemerin was quantified by ELISA in control (n = 80) and GDM (n = 40) patients and correlated to clinical and biochemical measures of renal function, glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
46
5
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 49 publications
7
46
5
11
Order By: Relevance
“…Results indicated that high chemerin levels were correlated with key MetS markers such as elevated levels of BMI, serum TG and blood pressure. This is consistent with other studies that also reported a significant association of serum chemerin levels with multiple compounding factors of MetS (3,12,13). These findings indicate that chemerin may play an important role in the mechanism of MetS and might be a potential independent adipocytokine marker of MetS.…”
Section: Discussionsupporting
confidence: 92%
“…Results indicated that high chemerin levels were correlated with key MetS markers such as elevated levels of BMI, serum TG and blood pressure. This is consistent with other studies that also reported a significant association of serum chemerin levels with multiple compounding factors of MetS (3,12,13). These findings indicate that chemerin may play an important role in the mechanism of MetS and might be a potential independent adipocytokine marker of MetS.…”
Section: Discussionsupporting
confidence: 92%
“…However, some researchers proposed different opinion that serum chemerin is not affected by GDM. They explained that this may ascribe to a good metabolic control of the GDM women [20][21][22]. Besides different metabolic control of the GDM women, the discrepancy of our results from these studies may attribute to different time point of blood sampling.…”
Section: Discussioncontrasting
confidence: 54%
“…Pfau et al found that serum chemerin levels were not significantly different in subjects with GDM as compared to healthy pregnant controls. He presumed circulating chemerin might well be increased in a more severe form of GDM [21]. Van Poppel et al demonstrated that the maternal circulation in pregnancy was determined by maternal obesity status, but not affected by GDM [22].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Germany reported that circulating levels of chemerin did not show a significant difference between pregnant women with GDM and healthy pregnant controls (1). Garces et al (23) found no significant association of insulin and HOMA levels with chemerin, as did other independent studies (11,24,25). We found similar results for chemerin in pregnant women with GDM; however, other studies presented an association of chemerin with insulin resistance in pregnancy (26,27).…”
Section: Discussionsupporting
confidence: 83%